CHAPTER: ROLE OF ALL INDIA UNITED DEMOCRATIC FRONT (AIUDF) IN ASSAM. - Talukdar., DR. Subhash (International Journal of Modern Agriculture, 2020)
Party system is the important factor in the working of representative form of Government. India is a democratic state. In the democratic state, political parties are said to be the life – blood of democracies. Modern democracies are indirect in character. They can function with the help of political parties. In the absence of political parties democracy cannot deliver the goods. Well organized political parties constitute the best form of democracy. India has the largest democracy in the world. It introduced universal adult franchise as the basis of voting right in the country. Now the voting age has been lowered down to 18. Most of the Indian voters are not politically matured and they do not have the political education in the proper sense. Political parties in India are classified by the Election Commission of India. It was classified for the allocation of symbol. The Election Commission of India classified parties into three main heads: National parties, State parties and registered (unrecognized) parties. The Regional Political Parties are playing a very significant role in Indian political system, particularly in the post Congress era and in coalition politics. As far as the national level politics is concerned, the regional political parties play a ‘king maker’ role. Whereas, the politics at state level is concerned, the regional political parties have been playing an effective role for working of government machinery. The Assam has also not lagging behind this context. Although the state has produces some small political parties before 1985, but formation of the AGP, BPPF, BPF and the AIUDF playing a very significant role in the politics of Assam. The AGP and the AIUDF not only emerge as an alternative of the Congress party at the state politics but also could able to participate in the national politics. Following are the reasons for the growth of regional parties in Assam -